Use of noninvasive ventilation after discontinuation of invasive - Distéfano, Eduardo; Destefanis, Claudia; Gaggioli, Matías; Botto, Magdalena; Villafañe, María Celeste; Báez, Gretel; Forcillo, Marcos; Bertozz, Sebastián; Silvina Picón Fuster, Silvina (Revista del Hospital Italiano de Buenos Aires, 2020)
Introduction: the discontinuation of invasive mechanical ventilation in the intensive care unit is a fundamental and primary objective, both ofwhich aim to avoid the complications associated with it. The use of non-invasive ventilation in this context may follow three specific scenarios:a) as prevention of extubation failure, b) as interface change, c) in overt failure. There is not enough evidence on the time of use of NIV in thissubpopulation, the variables used to guide its use, the causes of NIV failure and the associated mortality in these patients.Objectives: to describe the use of NIV after extubation in adult critically ill patients. Further, we aim to describe the time of NIV use, the mortalityand reintubation rate of each subgroup.Materials and methods: retrospective cohort study including adult patients admitted to the ICU at Hospital Italiano de San Justo, who receivedNIV post-extubation. Using the electronic health database, epidemiological variables were recorded prior to admission to the ICU and follow-updata during the hospitalization. The period analyzed was from December 17, 2016 to August 1, 2018.Results: 48 patients were included in the present analysis. Median age was 76 years (RIQ 62.75-83.25) and 58.33% were men. The Charlsoncomorbidity index had a median value of 5 (RIQ 3-6). Of the total number of patients recruited, 33 used NIV as prevention of extubation failure(68.75%), 13 as interface change (27.08%). ) and only 2 as overt extubation failure (4.16%).The median number of days of NIV use was 1 (RIQ0-5) in failure prevention and 1 (RIQ 1-2) in the change of interface group. 8 patients were reintubated (16.66%). 9.1% and 7.7% of patients diedin the groups that used NIV as prevention of extubation failure and change of interface respectively.Conclusions: NIV is frequently used in adult patients following extubation in our centre. Further studies are warranted to depict the necessary timeof use to better allocate resources within the intensive care unit
Keywords: ventilation; extubation; intensive; intensive care uni; mortality; reintubation